EMG synchrony to assess impaired corticomotor control of locomotion after stroke. (December 2017) - Lodha, Neha; Chen, Yen-Ting; McGuirk, Theresa E.; Fox, Emily J.; Kautz, Steven A.; Christou, Evangelos A.; Clark, David J.
Abstract: Adapting one's gait pattern requires a contribution from cortical motor commands. Evidence suggests that frequency-based analysis of electromyography (EMG) can be used to detect this cortical contribution. Specifically, increased EMG synchrony between synergistic muscles in the Piper frequency band has been linked to heightened corticomotor contribution to EMG. Stroke-related damage to cerebral motor pathways would be expected to diminish EMG Piper synchrony. The objective of this study is therefore to test the hypothesis that EMG Piper synchrony is diminished in the paretic leg relative to nonparetic and control legs, particularly during a long-step task of walking adaptability. Twenty adults with post-stroke hemiparesis and seventeen healthy controls participated in this study. EMG Piper synchrony increased more for the control legs compare to the paretic legs when taking a non-paretic long step (5.02 ± 3.22% versus 0.86 ± 2.62%), p < 0.01) and when taking a paretic long step (2.04 ± 1.98% versus 0.70 ± 2.34%, p < 0.05). A similar but non-significant trend was evident when comparing non-paretic and paretic legs. No statistically significant differences in EMG Piper synchrony were found between legs for typical walking. EMG Piper synchrony was positively associated with walking speed and step length within the stroke group. These findings support the assertion that EMG Piper synchrony indicates corticomotor contribution to walking.